Assessment of Interns' Knowledge on Diagnosis of Emergencies in Hemodialysed Patients before and after Training - Mohammad Reza Ardalan; Hamid Noshad; Parviz Saleh; Jalal Etemadi (Tabriz University of Medical Sciences, 2012)
Introduction: It is apparent that having a good inflammation in hemodialysis indications, methods of the procedure, recognition of the complications are common mistakes in emergency and internal medicine and they are life saving for patients most of the times. It is clear that our medical students have many problems in this field (hidden curriculum). Therefore, we decided to do a study on the subject. Methods: During 2011, forty interns of nephrology ward enrolled in this study. They filled a questionnaire containing questions about their general hemodialysis knowledge before passing the classes. After having six one -hour classes on HD essentials, complications and emergencies, they filled the questionnaire again. The data analyzed using paired t-test and the reported Mean ± SD P< 0.05 considered significant. Results: The interns were satisfied in all the trained aspects like general hemodialysis knowledge (P< 0.001), dialysis essentials (P<0.001), physical examination (P<0.001), AVF examination (P< 0.001), volume reduction (P< 0.001), anticoagulation (P<0.001), AVF failure management (P<0.001), HD complications (P<0.001), device setting (P<0.001), cannulation (P< <0.001), dialysis efficacy (P< 0.001) and capability of patients education(P<0.001). Conclusion: Medical students had many problems with HD so that teaching of most essential aspects of hemodialysis can improve their knowledge which can be life saving in emergency situations.